Effects of galectin-1 inhibitor OTX008 on oral squamous cell carcinoma cells in vitro and the role of AP-1 and the MAPK/ERK pathway. (February 2022) - Greer, Philippa F.C.; Rich, Alison; Coates, Dawn E.
Abstract: Objective: To investigate the in vitro effects of inhibiting galectin-1 using the small-molecule inhibitor OTX008 on oral squamous cell carcinoma (OSCC) cell lines and the role of the MAPK pathway. Methods: One normal oral keratinocyte (NOK) and three OSCC cell lines were cultured in vitro and the expression of galectin-1 protein by each quantified using ELISA. Cell lines were treated with galectin-1 (50, 100 and 150 ng/mL) or OTX008 (12.5, 25, 50 and 100 μg/mL) and cell viability assayed (n = 3). OSCC cell lines with and without 25 μg/mL OTX008 (n = 3) treatment for 48 h, were analysed using qRT 2 -PCR with a custom array, to assess relative gene expression. Results: All cell lines were found to express galectin-1 protein. Exogenous galectin-1 significantly reduced cell viability in one OSCC cell line over time while the others were only minimally affected. OTX008 treatment reduced cell viability in a dose and time-dependent manner in all cell lines and this was associated with significant regulation of FOS gene expression in the OSCC cell lines. Conclusion: OTX008 decreased the viability of OSCC and NOK cells in a dose-dependent manner. The significant regulation of FOS suggests OTX008 causes early induction of the MAPK pathway via the immediate response gene FOS as a subunit of the AP-1 complex. Highlights: Galectin-1 protein is expressed by oral squamous cell carcinoma (OSCC) cells. Exogenous addition of galectin-1 had minimal effect on OSCC cell viability. OTX008 significantly reduced OSCC cell viability in time and dose manner. The FOS gene was regulated in all cell lines treated with OTX008. OTX008 may provide a synergistic or additive therapy with traditional approaches.